Effectiveness of Telehealth in Improving Quality of Life and Lowering Depression in Post-Stroke Patients: A Meta-Analysis - Siti Luluk Khamidahtun Ni'mah; Didik Tamtomo; Bhisma Murti (Masters Program in Public Health, 2023)
Background: People who have a stroke are generally more likely to have difficulty managing daily activities such as walking, bathing, dressing, and participating in activities in the community and showing symptoms of depression that affects the quality of life. Telehealth is here to help people communicate with health workers without having to come directly to health facilities. The study aims to analyze how much effect telehealth has in improving the quality of life and reducing the risk of depression in post-stroke patients.Subjects and Method: This was a meta-analysis study using PICO. Population: post-stroke patients. Intervention: telehealth. Comparison: no telehealth. Outcome: quality of Life and depression. This study used articles from several databases namely Pubmed, Google Scholar, Science Direct, and Cochrane Library using the keywords